2020
DOI: 10.3390/ijerph17155281
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Periodontal Status between Females Referenced for Fertility Treatment and Fertile Counterparts: A Pilot Case–Control Study

Abstract: Studies investigating the periodontal status of women seeking fertility treatment have never been conducted. The purpose of this pilot study was to compare the periodontal status among females referenced to a Fertility Clinic (FC) when compared to matched females from a representative regional epidemiological sample. Our secondary aims were to investigate if periodontal clinical measures differ between these two groups of females and how they impact on oral health-related quality of life (OHRQoL). We enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 87 publications
1
6
2
4
Order By: Relevance
“…In our study, the PISA and PESA values were higher in women with unexplained infertility than in fertil women. This findings were similar to previous pilot study that found the infertile participants presented significantly higher values of PESA than fertile women 28 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the PISA and PESA values were higher in women with unexplained infertility than in fertil women. This findings were similar to previous pilot study that found the infertile participants presented significantly higher values of PESA than fertile women 28 …”
Section: Discussionsupporting
confidence: 92%
“…This findings were similar to previous pilot study that found the infertile participants presented significantly higher values of PESA than fertile women. 28 In a recent study involving 3416 women, in which the relationship of periodontitis with female infertility was evaluated in terms of the time to conception. The time to conception has been reported to be delayed more than 12 months in non-Caucasian women associated with a higher prevalence of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we can explain a smaller number of positive tests. This is inconsistent with published studies that have shown poorer periodontal status in patients with idiopathic infertility (1,8,10,12). A possible explanation might be that infertile women included in our study were more aware of their oral health, or that they had different economic or educational background which might also affect their oral health, which was not considered in this study.…”
Section: Raspravacontrasting
confidence: 98%
“…Na temelju naših rezultata moramo odbaciti tu hipotezu jer su rezultati pokazali da su pacijentice s idiopatskom neplodnošću imale blaži stupanj parodontitisa nego kontrolna skupina, te time možemo objasniti manji broj pozitivnih testova. To je proturječno objavljenim istraživanjima koja su pokazala lošiji parodontni status pacijentica s idiopatskom neplodnošću (1,8,10,12). Moguće objašnjenje za to može biti da su neplodne žene uključene u naše istraživanje bile svjesnije svojega oralnoga zdravlja ili da su imale različitu ekonomsku ili obrazovnu pozadinu, što bi također moglo utjecati na njihovo oralno zdravlje, no to nije uzeto u obzir u ovoj studiji.…”
Section: Raspravaunclassified
See 1 more Smart Citation